VIBRASI PIKIRAN, KERUSAKAN OZON DAN BENCANA ALAM SATU KESATUAN SISTEM KESADARAN KOSMOS: Perspektif Teo-Kosmologis Post Metafisika - I Ketut Donder (Sanjiwani: Jurnal Filsafat, 2018)
The Vedas have various concepts and theories about the creation of the universe. Vedic concepts are accepted by revelation, while Vedanta theories are created through contemplative research on macrocosms and microcosms. Creation theories in Vedanta, are: Manah theory or the theory of Virat, this theory states that the universe created from the mind of God. The second is the theory of Sabda, this theory states that the universe is created from the Voice of God, this theory is similar to the Big Bang theory. Other theory is the theory of Apah, this theory states that the universe came from water, and there are also many other theories. These theories seem to be compatible with modern scientific theories. This shows that the Vedic teachings have been an inspiration for scientists. The Manah theory, sabda theory, Apah theory, and other theories are embedded by Hiranyagarbha theory. This theory states that the human mind, the mind of the cosmos, and the human mind, historically-theo-cosmologically, have a very close relationship. Hiranyagarbha theory that became the foundation of Hindu Cosmology describes that before the universe was created, there was an element of astaprakriti, the eight subtle elements without size (tan matra). The eight supernatural elements are buddhi (intellect), manas (mind), ahamkara (ego), akhasa (ether), vayu (air), teja (fire), apah (water), and pritivi (land), all within the warehouse. The universe is called Hiranyagarbha. Based on the Hiranyagarbha theory, the creation of the macrocosm begins with the consciousness of God, then moves the mind of God (Manas) connected to the manas that is on Hiranyagarbha. After the macrocosm, humans were created, then the mind of God, the mind of the cosmos, and the human mind have connectivity with each other. Therefore, do not ever think negative about anything.